Impact Evaluation in International Development : Theory, Methods and Practice - Glewwe, Paul; Todd, Petra (Washington, DC: World Bank, 2022)
Impact evaluations are studies that attempt to measure the causal impact of a project, program, or policy on one or more outcomes. This book provides a comprehensive exposition of how to conduct impact evaluations.